(untitled) (Mustansiria Dental Journal, 2018)
Background and objectives: The aim of root canal obturation in endodontic treatment is to prevent communication between the oral cavity and periapical tissues. Several techniques had been introduced to achieve complete filling of the root canal system. It had been noted that more researches are needed to establish standard techniques of root canal filling, and all the techniques should be compared for filling root canals. The aim of this study was to compare the apical sealing ability of three different obturation techniques. Methods: Thirty single rooted teeth were collected and randomly divided into three groups. There were 10 teeth in each group. The teeth were obturated by gutta percha as follows: Groups 1 with Thermafil, Groups 2 with Soft core, and Groups 3 with System B. The apical leakage in these groups was evaluated using a dye penetration method. Results: The lowest mean rank of leakage was observed for system B and the highest was observed for the thermafil groups. The difference between Thermafil, soft core and system B was statistically not significant by using Kruskal Wallis test. Conclusion: System B obturation technique show less microleakage than soft core and thermafil techniques although the differences was not significant.